Influência do cultivo da cana-de-açúcar nas nascentes do alto e baixo rio Japaratuba - Lima, Josiene Ferreira dos Santos (2013)
The most aggravating factors in the context of agricultural activities correspond to the indiscriminate use of water, so it is necessary to take measures in relation to the actions of environmental damage related to predatory acts on the man / nature. Address issues that involve human actions on water takes us to a complex challenge, since there are numerous possibilities to approach. In this context, the research aimed to evaluate the influence of the cultivation of sugar cane in the headwaters of the Planning Units called Upper and Lower River Japaratuba. The research qualitative descriptive exploratory owned. For classification and conservation status of the springs was applied the methodology described in Pinto et al. (2004). Interviews were carried out in six municipal environmental agencies, questionnaires to communities around the sugar cane, and physical-chemical analysis of water and pesticide residues. The springs addressed and discussed in this research, although distinct from each other by several particularities regarding preservation strategies, present as basic points common the presence of cane sugar, the main use for irrigation and little recovery work. The forests are still preserved the springs seem to be "sandwiched", "suffocated" by the action sugarcane. It was observed that the properties before they grew another subsistence crop, began to cultivate sugar cane influenced by industry and the market. The region was driven by the consumer market outside of the derivatives of cane sugar. It was found that natural resources are subtracted and little monitored, the municipal environmental agencies do not absorb this responsibility. The physico-chemical analyzes showed traces of the use of vinasse, however, the analysis of pesticide residues was not observed in the presence of pesticide samples. In this context there is a need to monitor the water sources in the region and develop work and actions to mitigate the impacts caused by the sugarcane industry in the study area.